Virtual reality experiences, attachment and experiential outcomes in tourism. Issue 3 (17th November 2019) - Wu, Hung-Che; Ai, Chi-Han; Cheng, Ching-Chan
Abstract : Purpose: The purpose of this study is to examine the structural relationships between the dimensions of virtual reality (VR) experiences (immersion, interaction, usability and illusion), the dimensions of VR attachment (VR dependence, VR identity, VR affect and VR familiarity) and the dimensions of VR experiential outcomes (VR experiential satisfaction, VR experiential loyalty and VR experiential advocacy). Design/methodology/approach: A total of 490 visitors who tried 360 VR travel video games in the TripMoment VR were surveyed. Findings: In this study, there are positive relationships between VR experiential satisfaction and immersion, interaction, illusion, as well as VR identity, VR affect and VR familiarity. In addition, VR experiential satisfaction has a positive relationship with VR experiential loyalty. In addition, VR experiential advocacy has a positive relationship with both VR experiential satisfaction and VR experiential loyalty. Practical implications: The results show that tourism operators should focus on increasing VR experiential satisfaction and experiential loyalty to enable visitors to have intentions to advocate their VR experiences. Originality/value: This paper provides the data that lead to a better understanding of the relationship between the dimensions of VR experiences, VR attachment and VR experiential outcomes in the tourism industry. Abstract : 旅游中的虚拟实境体验、依附和体验结果 目的: 本研究目的是在检验虚拟实境体验维度(沉浸、交互作用、可用性与幻觉), 虚拟实境依附维度(虚拟实境依赖、虚拟实境认同、虚拟实境影响与虚拟实境熟悉度)和虚拟实境体验结果维度 (虚拟实境体验满意度、虚拟实境体验忠诚度与虚拟实境体验主张)之间的结构关系。 设计/方法学/方法: 在时刻旅行中, 共受访490名游客尝试了360度虚拟实境旅游视频游戏。发现 – 在本次研究中, 虚拟实境体验满意度与沉浸、交互作用、幻觉与虚拟实境认同、虚拟实境影响与和虚拟实境熟悉度均存在正向关系。而且, 虚拟实境体验满意度对虚拟实境体验忠诚度有正向影响。此外, 虚拟实境体验主张对虚拟实境体验满意度与虚拟实境体验忠诚度两者均有正向影响。 实际意涵: 结果显示, 为了能使游客有意愿宣传自己的虚拟实境体验, 旅游经营者应该将焦点放在提升虚拟实境体验满意度与虚拟实境体验忠诚度。 原创/价值: 本文提供的数据有助于更好地理解旅游行业虚拟实境体验, 虚拟实境依附与虚拟实境体验结果维度之间的关系 Abstract : Experiencias de realidad virtual, apego y resultados experimentales en turismo Propósito: El objetivo de este estudio es examinar las relaciones estructurales entre las dimensiones que afectan a la VR: las experiencias (inmersión, interacción, usabilidad e ilusión), las dimensiones del apego (dependencia de VR, identidad de VR, afecto de VR y familiaridad de VR) y las dimensiones de los resultados experimentales (satisfacción experiencial de realidad virtual, lealtad experiencial de realidad virtual y defensa experiencial de realidad virtual). Diseño/metodología/enfoque: Se encuestó a un total de 490 visitantes, que probaron los videojuegos de viaje de 360 VR en TripMoment VR. Resultados: En este estudio, demuestra la existencia de relaciones positivas entre la satisfacción experimental de la realidad virtual y la inmersión, la interacción, la ilusión, así como la identidad de la realidad virtual, el efecto de la realidad virtual y la familiaridad de la realidad virtual. Además, la satisfacción experiencial, tiene una relación positiva con la lealtad experiencial, en la realidad virtual. Además, la defensa de la experiencia de VR tiene una relación positiva tanto con la satisfacción de la experiencia de VR como con la lealtad de la experiencia de VR. Implicaciones prácticas: Los resultados muestran que los operadores turísticos deberían centrarse en aumentar la satisfacción y la lealtad experiencial de la realidad virtual, para permitir que los visitantes tengan intenciones de defender sus experiencias en los contextos de la misma. Originalidad/valor: Este trabajo proporciona datos, que conducen a una mejor comprensión de la relación entre las dimensiones de las experiencias de realidad virtual, el apego a la realidad virtual y los resultados experimentales en la industria del turismo.